Prevention of Child Abuse and Maltreatment for Sociocultural Sustainability in Japan and Finland – with Special Reference to Child Homicide - Takahashi, Mutsuko (European Journal of Sustainable Development, 2025)
This research explores possibilities of enhancing sociocultural sustainability in precarious world with focus on issues on early prevention of child maltreatment in some developed countries. Although child maltreatment tends to be perceived as harm suffered by children at individual and family levels, plenty of research show that the position of children in society and the ways of child-rearing children reflect fundamental social norms and values. Relevant data are collected from a variety of former studies and related documents by literary analysis, and the issues and social discourses on child homicide (abuse death) are discussed. As concrete examples, the situations of and challenges with child homicide, especially infanticide and neonaticide, in Japan and Finland will be studied. Both countries have reached the best level in terms of infant mortality rate. Finland has remarkably reduced infanticide in the late twentieth century, whereas in Japan there is much to be done for improving reproductive rights and promoting children’s rights. In conclusion, proper and pertinent policy intervention accompanied with critical and constructive reviews on social norms of childbirth, family and child-rearing will contribute to individual well-being of children and families as well as sociocultural sustainability. Keywords: child abuse and maltreatment, infanticide, neonaticide, prevention, reproductive rights